2014
DOI: 10.3390/su6128432
|View full text |Cite
|
Sign up to set email alerts
|

A Scale-Explicit Framework for Conceptualizing the Environmental Impacts of Agricultural Land Use Changes

Abstract: Demand for locally-produced food is growing in areas outside traditionally dominant agricultural regions due to concerns over food safety, quality, and sovereignty; rural livelihoods; and environmental integrity. Strategies for meeting this demand rely upon agricultural land use change, in various forms of either intensification or extensification (converting non-agricultural land, including native landforms, to agricultural use). The nature and extent of the impacts of these changes on non-food-provisioning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…After significant floods in southeastern New Hampshire during 2006 and 2007, observed chloride concentrations across a broad range of discharge were distinctly lower, suggesting flushing of legacy chloride from the fifth‐order watershed (Daley et al, 2009). The mechanisms that control the dilution of road salt at affected reaches should be considered as an important secondary predictor of potential habitat degradation (Hale et al, 2014). Mechanisms that can influence dilution potential from clean headwaters include drinking and irrigation water abstractions in headwaters, and storage behind recreational dams.…”
Section: Resultsmentioning
confidence: 99%
“…After significant floods in southeastern New Hampshire during 2006 and 2007, observed chloride concentrations across a broad range of discharge were distinctly lower, suggesting flushing of legacy chloride from the fifth‐order watershed (Daley et al, 2009). The mechanisms that control the dilution of road salt at affected reaches should be considered as an important secondary predictor of potential habitat degradation (Hale et al, 2014). Mechanisms that can influence dilution potential from clean headwaters include drinking and irrigation water abstractions in headwaters, and storage behind recreational dams.…”
Section: Resultsmentioning
confidence: 99%
“…Local socio-economic factors can be overlooked at a larger scale, thereby reducing the spatial heterogeneity of ES. Drivers of environmental change exhibit scale sensitivity 35 , and although anthropogenic drivers can operate at multiple administrative scales, the impact of human activity tends to attenuate across scales 65 . On the whole, physical environments generally determine the fundamental characteristics of ES supply and control their general spatial distributions, whereas socio-economic factors influence local scale ecological processes 24 and result in higher spatial heterogeneity of ES.…”
Section: Discussionmentioning
confidence: 99%
“…While agriculture can improve the health, economics, and energetic aspects of society, it may also result in critical consequences for the environment, either through emissions of greenhouse gas or reduction in the quantity and quality of water and soil [12][13][14][15]. According to several studies [16][17][18], higher rates of damage to the environment tend to occur in regions with low per capita income.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, several authors (e.g., Wang and Qiu [21]) have reported that agriculture is responsible for more than 70% of deforestation. Framework and index approaches have been developed for assessing environmental sustainability in agriculture [14,15,22], in an effort to implement policies to reduce agricultural pollution.…”
Section: Introductionmentioning
confidence: 99%